Investment Needs Analysis in Pekanbaru City In 2023 - Ramadin Ramadin (LAFADZ JAYA Publisher, 2022)
The development of investment is one indicator of the progress of economic growth in Indonesia, where investments made properly can support the improvement of the welfare of the Indonesian people. The challenge of implementing investment in Indonesia today, one of which is the implementation of regional autonomy in Indonesia. The investment performance of a region can be reflected in the Capital Output Ratio (COR) and Incremental Output Ratio (ICOR). The development of the availability of investment in an area can be measured from the Capital Output Ratio (COR) which is the ratio between realized investment and the income of a region or GRDP. Meanwhile, the amount of investment capacity of a region in increasing any increase in regional income can be measured from the Incremental Capital Output Ratio (ICOR). If you look at the development of ICOR in Pekanbaru City, it has fluctuated, in 2016 it rose to 15.62 then in 2017 it decreased to 14.27, then in 2018 it became 15.57 and in 2019 it increased to 13.27 and in 2020 it decreased to -17.33 this is influenced by the Covid 19 Pandemic factor which causes all business sectors to slow down, in 2021 with a value of 15.87. From the results of the analysis of the Projection Investment Needs formulation, it is found that the investment needs in the city of Pekanbaru as much as Rp. 129 682.91 billion, it can be seen that the Base sector is in dire need of investment in 2023, which is 65.4%, the Business Fields are Manufacturing, Construction, Wholesale and Retail Trade., Car and motorcycle repair.